Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/cne.10905
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein expression and colocalization with calretinin, parvalbumin, and somatostatin in the GAD67‐GFP knock‐in mouse

Abstract: ␥-aminobutyric acid (GABA)ergic neurons in the central nervous system regulate the activity of other neurons and play a crucial role in information processing. To assist an advance in the research of GABAergic neurons, here we produced two lines of glutamic acid decarboxylase-green fluorescence protein (GAD67-GFP) knock-in mouse. The distribution pattern of GFP-positive somata was the same as that of the GAD67 in situ hybridization signal in the central nervous system. We encountered neither any apparent ectop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
1,341
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 1,169 publications
(1,425 citation statements)
references
References 54 publications
66
1,341
2
1
Order By: Relevance
“…To confirm that PlexinA1 is expressed in cortical interneurons, we used coronal sections from E14.5 GAD67‐GFP mice (Tamamaki et al, 2003b). Double labeling for PlexinA1 and GFP revealed colocalization in the mantle zones of the MGE and LGE as well as in the IZ and MZ of the cortex (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm that PlexinA1 is expressed in cortical interneurons, we used coronal sections from E14.5 GAD67‐GFP mice (Tamamaki et al, 2003b). Double labeling for PlexinA1 and GFP revealed colocalization in the mantle zones of the MGE and LGE as well as in the IZ and MZ of the cortex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Animals (Scientific Procedures) Act 1986 and institutional guidelines. Wild‐type animals were C57/bl6J mice obtained from Charles River, Ltd. PlexinA1 −/− and GAD67‐GFP neo‐ mice were generated as described previously (Yoshida et al, 2006 [PMID: 17145500]; Tamamaki et al, 2003b [PMID: 14574680]). PlexinA1 mice were genotyped by polymerase chain reaction (PCR) with the following primers: WT‐forward (5′‐CCTGCAGATTGATGACGACTTCTGC‐3′), WT‐reverse (5′‐TCATGCAGACCCAGTCTCCCTGTCA‐3′), product size 200 bp; and mutant‐forward (5′‐GCATGCCTGTGACACTTGGCTCACT‐3′), mutant‐reverse (5′‐CCATTGCTCAGCGGTGCTGTCCATC‐3′), product size 600 bp.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 20 male GAD67-GFP knock-in mice (heterozygote) aged 12 weeks were used. It has been confirmed that GAD67-GFP knock-in mice exhibit normal growth, normal reproductive behavior, and no abnormality in the brains at macroscopic level (Tamamaki et al, 2003). All experimental procedures were approved by the Committee of Animal Use for Research and Education of the Fourth Military Medical University (Xi'an, P. R. China).…”
Section: Materials and Methods Animalsmentioning
confidence: 92%
“…The production of the GAD67-GFP knock-in mice has been already reported (Tamamaki et al, 2003). In this study, 20 male GAD67-GFP knock-in mice (heterozygote) aged 12 weeks were used.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation